Risk management in R&D project - Salleh, Nurul Azita; Hasnan, Norlena (UUM College of Business, 2008)
Industries that relied heavily on internal development of new products face difficult challenges when planning R&D project portfolios for new products.Due to the uncertain nature of innovation, each R&D project undertaken for developing a new product has a degree of risk of failure which is significant and potentially very high.Major causes for project failure are faults, unpredicted changes and the unforeseen impossibilities of the objectives. Hence, this paper aims to highlight measures in managing risk in the early stage of new product development (NPD), particularly the R&D of the product. This paper also discusses the R&D management implication to technological innovation.